Oligomer-salt derived 3D, heavily nitrogen doped, porous carbon for Li-ion hybrid electrochemical capacitors application - Gokhale, Rohan; Aravindan, Vanchiappan; Yadav, Prasad; Jain, Srashti; Phase, Deodatta; Madhavi, Srinivasan; Ogale, Satishchandra (Carbon, 2014)
3D high surface area porous carbon is seen to form via self assembly of porous graphene sheets by direct pyrolysis of an oligomer salt tailored for the realization of molecular level activation. The oligomer salt was derived from 4-amino benzoic acid as the monomer by a facile free radical polymerization process. Incorporation of the functional groups (-COONa) eliminate the need for any external activating agents (KOH, ZnCl2, etc.) and also render high degree of sub-nanoscale homogeneity. This oligomer derived carbon (ODC) exhibits efficient performance in non-aqueous charge storage application namely Li-ion hybrid electrochemical capacitor (Li-HEC) owing to its high surface area, 3D interconnectivity and an appropriate pore size distribution. The Li-HEC fabricated with ODC based electrodes delivered a maximum energy density of similar to 63 Wh kg(-1) with spinel L4Ti5O12 as the anode. (C) 2014 Elsevier Ltd. All rights reserved.